Taking the bait understanding Filipino Generation Z’s meaning-making of foreign-produced video blogs on Philippine culture. - Garcia, John Mark Diwa; Vinculado, Jane O. (Quezon City College of Mass Communication, University of the Philippines, 2023)
The widespread emergence of the Pinoybaiting phenomenon is described as a localized pursuit of Western producers through video blogs (vlogs) to exploit the country's cultural appurtenances to amass Filipino audiences for economic gain.

To unpack how Filipinos, through the lens of Generation Z as the leading social media-consuming demographic, interpret this phenomenon, individual semi-structured interviews were held with six (6) UP College of Mass Communication students which employed Marian Friestad and Peter Wright's (1994) persuasion knowledge model and Henry Jenkins' (2009) theory on participatory culture. Moreover, using Virginia Braun and Victoria Clarke's (2006) theoretical thematic analysis, it was underscored how Pinoybaiting is deemed by Filipino Gen Z as an exploitative commoditization of Filipino culture built on exoticizing local culture and forging a mutualistic relationship with Filipinos. Key themes and tropes like Filipino-centered visual packaging, profound display of patronizing emotions, and lack of authenticity and apt knowledge on the Philippines were posited. Ultimately, the Filipinos' intrinsic pride, desire for Western validation, and mere leisure and entertainment are the identified thrusts of Filipinos' general consumption of Pinoybaiting videos.

Keywords: vlogs, Pinoybaiting, persuasion knowledge model, participatory culture
Ang malawakang pag-usbong ng penomenonang Pinoybaiting ay inilalarawan bilang paglikha ng mga kanluraning prodyuser ng video blogs (vlogs) upang gamitin ang lokal na kultura sang maenganyo ang mga Pilipino na sila ay tangkilikin dahil sa pinansyal na benepisvo na kaakibat nito sa mga dayuhang prodyuser. Upang maunawaan ang interpretasyon ng mga Pilipino sa Pinoybaiting Si pamamagitan ng mga Generation Z, na nangungunang konsyumci ng social media, nagsagawa ng mga interbyu sa arum na matt-aaral ng Kolehlyo ng Komunikasyong. Pangmadla ng Unibcrsidad ng Ptlipinas ukol sa pcnotnena. Ang mga nasabing panayam ay ginabayan ng p•rvuastun kluncle44,y nut:, Niarlan Frirstad and Peter Wright (1994) at ng tcxxyang partici/km, (vIrur.- ni 11 citt) Jenkins (2009) Gamic nn ang theo,n,,,/ tuna Virginia Ilium at Victoria Clarke (2006), Intim.% ang pagiuktt■ bilmg mapagsamantalang komoditisasyon eksonsisas) on ng mga lokal na kultura na niusasagawa sa pagbuo n mutualistik na ugna■-an sa mga Palm,' I inuko■ dm ang btswal na aspeto ng mga bidyo, hangad na pandaigdigang balidasyon, at ang intensyon ng mga manonood na rnabigyang-alive mga pangunahing motibo ng pagkonsumo ng. mga Pilipino_
Keywords: vlogs, Pinoybaiting. persuasion knowledge model, participatory culture
Vita.
Thesis
Includes bibliographical reference and appendices.
Keywords: Persuasion (Psychology); Online social networks